Positive electrode material and preparation method and application thereof

By modifying nickel oxide on the surface of the positive electrode material of the sodium ion battery, a stable solid electrolyte interface is formed, which solves the problem of adverse reactions between the electrode and the electrolyte interface, and significantly improves the cyclic stability and kinetic performance of the sodium ion battery.

CN119153666APending Publication Date: 2024-12-17SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411539705.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The electrochemical performance of existing sodium ion battery positive electrode materials is affected by adverse side reactions between the electrode and the electrolyte interface, electrolyte decomposition and transition metal ion dissolution, resulting in insufficient cycle life.

Method used

A nickel oxide modification layer is used to enhance the mechanical strength and catalytic characteristics of the positive electrode material, form a stable solid electrolyte interface, inhibit the occurrence of surface side reactions, and modify nickel oxide on the surface of the positive electrode matrix material by co-precipitation method.

Benefits of technology

It effectively suppresses adverse side reactions between the electrode and the electrolyte, improves the cycle stability and kinetic performance of the positive electrode material, extends the cycle life of the battery, and increases the maximum discharge capacity of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153666A_ABST
    Figure CN119153666A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a positive electrode material and a preparation method and application thereof. The positive electrode material comprises a positive electrode base material and a nickel oxide modification layer positioned on the surface of the positive electrode base material, the positive electrode base material comprises a layered transition metal oxide material, the chemical general formula of the layered transition metal oxide material is NaqMbDcO2, 0.59 < = q < = 1, 0.7 < = b < = 1, 0 < = c < = 0.3, b + c = 1, M is a transition metal element, and D is a metal doping element. According to the positive electrode material, the nickel oxide modification layer is high in mechanical strength, cracking and breaking of particles can be restrained to a certain extent, the nickel oxide modification layer has the good catalytic characteristic, formation of a stable solid electrolyte interface is accelerated, surface side reactions can be restrained, and the cycling stability of the positive electrode material is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a positive electrode material and a preparation method and application thereof. Background Art

[0002] Among the many energy storage technologies, secondary batteries are particularly prominent, showing broad prospects as an energy storage medium. They are widely used in portable electronic devices and large-scale electrochemical energy storage scenarios due to their environmentally friendly, flexible, easy to maintain and efficient conversion characteristics. In particular, lithium-ion batteries (LIBs) have attracted much attention and become popular in various fields due to their excellent energy density, high average operating voltage and large capacity characteristics. However, considering that lithium accounts for a very small proportion of global resources (about 0.01%) and is extremely unevenly distributed, coupled with high mining and transportation costs, it has become a top priority to seek to develop new rechargeable batteries that can effectively replace lithium-ion batteries based on abundant and cost-effective resources.

[0003] Among the wide range of energy storage technology candidates, sodium-ion batteries (SIBs) have shown significant development potential. The abundance of sodium in the earth's crust is as high as 2.83%. It is not only abundant in resources but also widely distributed. Compared with lithium resources, the cost of obtaining sodium salts is lower, and the extraction process of metallic sodium is simpler and more environmentally friendly. From an electrochemical point of view, Na + The reduction potential of Na / Na relative to the standard hydrogen electrode (SHE) is -2.71 V, while Li + The reduction potential of / Li is -3.04V relative to the standard hydrogen electrode, making it a candidate with a similar operating voltage to lithium-ion batteries. The working mechanism of the two is similar, which makes sodium-ion batteries compatible with existing lithium-ion battery production lines and promotes the rapid transformation and application of technology. In addition, the design of sodium-ion batteries takes economic benefits into consideration. Since sodium and aluminum do not form alloys, cost-effective aluminum foil can be used to replace copper foil as the negative electrode current collector. This change directly reduces the production cost by about 8%. Moreover, the thermal management of sodium-ion batteries is more convenient, due to its higher internal resistance, which reduces heat generation and enhances the safety of use. Another significant advantage is that the high diffusion rate of sodium ions during battery cycling can inhibit the formation of lithium dendrites, which is common in lithium-ion batteries, thereby avoiding the risk of internal short circuits in the battery. Sodium-ion batteries show high safety when facing physical damage such as extrusion or puncture tests, without the risk of fire and explosion, further strengthening their advantages in safety performance. Given its cost-effectiveness and excellent charge and discharge rate, sodium-ion batteries are very suitable for large-scale energy storage systems, as well as starting power supplies and grid frequency regulation scenarios with high power requirements. Therefore, sodium-ion batteries are seen as a key element that can replace lithium-ion batteries in specific fields and promote the advancement of large-scale energy storage technology.

[0004] The current research on positive electrode materials for sodium-ion batteries mainly focuses on layered oxides, Prussian blue analogs, organic molecular materials, and polyanion compounds. The capacity retention rate and structural stability of Prussian blue analogs and polyanion compounds are better than other positive electrode materials, but the discharge capacity of both is unstable. Organic compounds have the problems of low solubility in electrolytes and low electrical conductivity. Layered oxide materials have high energy density, simple production process similar to LIBs, and are more environmentally friendly, so they have been widely studied.

[0005] Adverse side reactions at the electrode-electrolyte interface, such as problems at the cathode-electrolyte interface, electrolyte decomposition problems, electrode material particle surface reconstruction problems, and transition metal ion dissolution problems, are a major factor affecting the electrochemical performance of layered oxide materials. Fluoride salt solutes and organic solvents react with water to generate HF, which corrodes the electrode, causing ions on the positive electrode surface to dissolve, resulting in battery capacity decay. Transition metal ions dissolved in the electrolyte and cracks on the surface of the electrode material will destroy the stable cathode electrolyte interface, increase side reactions, and affect electrochemical performance. The surface reconstruction caused by electrode side reactions is usually manifested as randomly distributed rock salt / spinel phases and heterogeneous characteristics of dislocations, which hinder the local Na + The diffusion of electrons and the like will affect the cycle life. Therefore, reducing the interface side reactions is very important to improve the performance of layered oxide materials.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] One object of the present invention is to provide a positive electrode material to solve the above-mentioned technical problems. The positive electrode material of the present invention has a nickel oxide modified layer with high mechanical strength, which can inhibit the cracking and breakage of particles to a certain extent. The nickel oxide modified layer has good catalytic properties, accelerates the formation of a stable solid electrolyte interface, inhibits the occurrence of surface side reactions, and improves the cycle stability of the material.

[0008] Another object of the present invention is to provide a method for preparing the positive electrode material, which is simple to implement and environmentally friendly.

[0009] Another object of the present invention is to provide a positive electrode sheet.

[0010] Another object of the present invention is to provide a battery.

[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0012] A positive electrode material, comprising a positive electrode base material and a nickel oxide modification layer located on the surface of the positive electrode base material; the positive electrode base material comprises a layered transition metal oxide material, the chemical formula of the layered transition metal oxide material is Na q M b D c O2, wherein 0.59≤q≤1, 0.7≤b≤1, 0≤c≤0.3, and b+c=1, M is a transition metal element, and D is a metal doping element.

[0013] In some embodiments, the transition metal element includes at least one of Cr, Mn, Fe, Co, Ni and Cu.

[0014] In some embodiments, the metal doping element includes at least one of Li, Mg, Al, Zn, K, Ca, V, Ti, Nb, Zr and Sn;

[0015] In some embodiments, the molar ratio of elemental nickel in the nickel oxide modification layer to the positive electrode matrix material is (0.05-0.1):1.

[0016] In some embodiments, the layered transition metal oxide material is a layered manganese-based oxide material, and the chemical formula of the layered manganese-based oxide material is Na x Mn y M z O2, wherein 0.59≤x≤1, 0.7≤y≤1, 0≤z≤0.3, and y+z=1, and M is at least one of Fe, Co, Cu and Mg.

[0017] The method for preparing the positive electrode material as described above comprises the following steps:

[0018] The nickel compound solution is first mixed with the positive electrode matrix material to obtain a first system; the first system is second mixed with the precipitant solution to obtain a second system; the second system is solid-liquid separated, and the solid is collected and heat treated.

[0019] In some embodiments, the nickel-containing compound includes at least one of nickel chloride, nickel nitrate, nickel chloride hydrate, and nickel nitrate hydrate.

[0020] In some embodiments, the nickel-containing compound solution includes a nickel-containing compound and an alcohol solvent.

[0021] In some embodiments, the mass ratio of the nickel-containing compound to the positive electrode matrix material is (1-4.5): (15-25).

[0022] In some embodiments, the first mixing is performed by ultrasonic treatment, and the ultrasonic treatment time is 10 to 40 minutes.

[0023] In some embodiments, the precipitant solution includes an aqueous ammonia solution, a urea solution, an ammonium bicarbonate solution, a sodium carbonate solution, or a sodium hydroxide solution.

[0024] In some embodiments, the concentration of the precipitant solution is 1 to 4 mol / L.

[0025] In some embodiments, the mass ratio of the precipitant to the nickel-containing compound is (0.4-0.8):1.

[0026] In some embodiments, the second mixing specifically includes: dropping the precipitant solution into the first system, and then performing a third stirring to obtain the second system.

[0027] In some implementations, the temperature of the system for the second mixing of the first system and the precipitant solution is controlled to be 30 to 80° C., and the dripping time is 10 to 60 minutes.

[0028] In some implementations, the third stirring time is 2 to 10 hours.

[0029] In some embodiments, the heat treatment temperature is 450-600° C., and the heat treatment time is 4-10 hours.

[0030] In some embodiments, the heat treatment is performed in an atmosphere of air.

[0031] In some embodiments, before the heat treatment, the solid is dried at a temperature of 60 to 90° C. and for a time of 9 to 15 hours.

[0032] A positive electrode sheet comprises the positive electrode material.

[0033] A battery comprises the positive electrode sheet.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] (1) The positive electrode material of the present invention has a nickel oxide modified layer with high mechanical strength, which can inhibit the cracking and breakage of particles to a certain extent. The nickel oxide modified layer has good catalytic properties, accelerates the formation of a stable solid electrolyte interface, inhibits the occurrence of surface side reactions and the dissolution of manganese ions, and improves the cycle stability of the material; it can prevent adverse side reactions between the electrode and the electrolyte, and form a stable solid electrolyte interface on the electrode surface. This interface can prevent the electrolyte from corroding the electrode material, protect the positive electrode material from the influence of moisture and carbon dioxide in the air, stabilize its surface structure, and improve the stability of the electrode structure, thereby improving the cycle performance of the material.

[0036] (2) The method for preparing the positive electrode material of the invention is to modify nickel oxide on the surface of the positive electrode substrate material by a co-precipitation method, which is simple to operate and easy to control; the modification of nickel oxide can improve the pseudocapacitive behavior of the electrode reaction and improve the kinetic performance of the electrode.

[0037] (3) The battery of the present invention has excellent cycle stability and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0039] Figure 1 This is a transmission electron microscope image (TEM) of the positive electrode material in Example 4 of the present invention;

[0040] Figure 2 This is a transmission electron microscope image of the positive electrode material in Example 5 of the present invention. DETAILED DESCRIPTION

[0041] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0042] According to one aspect of the present invention, the present invention relates to a positive electrode material, comprising a positive electrode base material and a nickel oxide modified layer located on the surface of the positive electrode base material; the positive electrode base material comprises a layered transition metal oxide material, and the chemical formula of the layered transition metal oxide material is Na q M b D c O2, wherein 0.59≤q≤1, 0.7≤b≤1, 0≤c≤0.3, and b+c=1, M is a transition metal element, and D is a metal doping element.

[0043] The positive electrode material of the present invention can prevent adverse side reactions between the electrode and the electrolyte, and form a stable solid electrolyte interface on the electrode surface. This interface can prevent the electrolyte from corroding the electrode material, protect the positive electrode material from the influence of moisture and carbon dioxide in the air, stabilize its surface structure, and improve the stability of the electrode structure, thereby improving the cycle performance of the material.

[0044] In some embodiments, the value of q is 0.59, 0.6, 0.65, 0.7, 0.75, 0.8, 0.9, 0.95, 1, etc., the value of b is 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, etc., and the value of c is 0.05, 0.1, 0.15, 0.2, 0.25 or 0.3, etc.

[0045] In some embodiments, the transition metal element includes at least one of Cr, Mn, Fe, Co, Ni and Cu. In some embodiments, the transition metal element can be a combination of Cr and Mn, a combination of Fe and Co, a combination of Fe, Co and Ni, etc.

[0046] In some embodiments, the metal doping element includes at least one of Li, Mg, Al, Zn, K, Ca, V, Ti, Nb, Zr and Sn. In some embodiments, the metal doping element can be a combination of Li and Mg, a combination of Al and Zn, a combination of Nb, Zr and Sn, etc.

[0047] In some embodiments, the molar ratio of elemental nickel in the nickel oxide modification layer to the positive electrode matrix material is (0.05-0.1):1, for example, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.1:1, etc.

[0048] In some embodiments, the layered transition metal oxide material is a layered manganese-based oxide material, and the chemical formula of the layered manganese-based oxide material is Na x Mn y M z O2, wherein 0.59≤x≤1, 0.7≤y≤1, 0≤z≤0.3, and y+z=1, and M is at least one of Fe, Co, Cu and Mg.

[0049] According to another aspect of the present invention, the present invention also relates to a method for preparing a positive electrode material, comprising the following steps:

[0050] The nickel compound solution is first mixed with the positive electrode matrix material to obtain a first system.

[0051] The first system is mixed with the precipitant solution for a second time to obtain a second system.

[0052] The second system is subjected to solid-liquid separation, and the solids are collected and heat-treated.

[0053] The preparation method of the positive electrode material of the present invention is to modify the surface of the positive electrode base material with nickel oxide by a coprecipitation method. The nickel oxide modification layer has a large mechanical strength and can inhibit the cracking and breaking of particles to a certain extent. The nickel oxide modification layer has good catalytic properties, accelerates the formation of a stable solid electrolyte interface, inhibits the occurrence of surface side reactions and the dissolution of manganese ions, and improves the cycle stability of the material. The modification of nickel oxide can improve the pseudocapacitive behavior of the electrode reaction and improve the kinetic performance of the electrode. At high temperature, a small amount of nickel ions are doped into the positive electrode base material to increase the maximum discharge capacity of the electrode.

[0054] In some embodiments, the positive electrode matrix material can be prepared by solid phase method, sol-gel method, coprecipitation method, hydrothermal method, etc. The present invention adopts a simple solid phase method.

[0055] In some embodiments, the preparation method of the positive electrode matrix material comprises: weighing a sodium source, an element M source and an element D source in a certain stoichiometric ratio, mixing with a dispersant and then ball milling to obtain a mixed slurry, washing, drying, grinding, pre-burning, calcining the mixed slurry in sequence, and grinding after cooling to obtain a positive electrode matrix material. In some embodiments, the dispersant includes anhydrous ethanol, the dispersion medium is zirconium oxide, and argon is filled as a protective gas; the ball milling speed is 300r / min and the time is 12h. In some embodiments, anhydrous ethanol is used for washing. In some embodiments, the drying temperature is 60 to 85°C. The pre-burning temperature is 400 to 600°C and the time is 2h; the calcination temperature is 800 to 950°C and the calcination time is 10 to 15h. In some embodiments, cooling is performed by natural cooling to below 100°C.

[0056] In some embodiments, the nickel-containing compound includes at least one of nickel chloride, nickel nitrate, nickel chloride hydrate and nickel nitrate hydrate. In some embodiments, the nickel-containing compound can be a combination of nickel chloride and nickel nitrate, a combination of nickel nitrate, nickel chloride hydrate and nickel nitrate hydrate, etc.

[0057] In some embodiments, the nickel-containing compound solution comprises a nickel-containing compound and an alcohol solvent. In some embodiments, the alcohol solvent is at least one of ethanol, isopropanol, and n-butanol.

[0058] In some embodiments, the mass ratio of the nickel-containing compound to the positive electrode matrix material is (1-4.5): (15-25).

[0059] In some embodiments, the first mixing is performed by ultrasonic treatment, and the ultrasonic treatment time is 10 to 40 minutes, such as 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes or 40 minutes.

[0060] In some embodiments, the precipitant solution includes aqueous ammonia, aqueous urea solution, aqueous ammonium bicarbonate solution, aqueous sodium carbonate solution or aqueous sodium hydroxide solution. A suitable precipitant solution is used to form a stable nickel oxide modification layer. The concentration of the precipitant solution is 1 to 4 mol / L, such as 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L or 4 mol / L.

[0061] In some embodiments, the mass ratio of the precipitant to the nickel-containing compound is (0.4-0.8):1.

[0062] In some embodiments, the second mixing specifically includes: adding the precipitant solution dropwise to the first system, and then performing a third stirring to obtain a second system. In some embodiments, the temperature of the system for controlling the second mixing of the first system and the precipitant solution is 30 to 80°C, such as 30°C, 40°C, 50°C, 55°C, 60°C, 70°C or 80°C. The time of the dropwise addition is 10 to 60 minutes, such as 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes, etc. The time of the third stirring is 2 to 10 hours, such as 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours. The present invention adopts a suitable second mixing condition to ensure a more uniform precipitation of the nickel-containing compound, and forms a uniform coating layer on the surface of the positive electrode substrate material to improve the electrochemical performance of the nickel oxide modified layer finally obtained.

[0063] In some embodiments, the heat treatment temperature is 450-600°C, such as 450°C, 460°C, 470°C, 480°C, 500°C, 520°C, 550°C, 560°C, 580°C, 600°C, etc., and the heat treatment time is 4-10h, such as 4h, 5h, 6h, 7h, 8h or 10h, etc. The heat treatment atmosphere is air. The present invention forms a nickel oxide modified layer with excellent performance through suitable heat treatment conditions.

[0064] In some embodiments, the solid is dried before the heat treatment. The drying temperature is 60 to 90° C., such as 60° C., 70° C., 80° C. or 90° C., etc.; the drying time is 9 to 15 hours, such as 9 hours, 10 hours, 11 hours, 12 hours or 15 hours, etc. The liquid is removed by suitable drying conditions.

[0065] According to another aspect of the present invention, the present invention also relates to a positive electrode sheet, comprising the above-mentioned positive electrode material.

[0066] The positive electrode sheet of the present invention comprises a positive electrode current collector and a positive electrode layer located on the surface of the positive electrode current collector, and the positive electrode layer comprises the above-mentioned positive electrode material, a conductive agent and a binder.

[0067] According to another aspect of the present invention, the present invention also relates to a battery, comprising the positive electrode sheet.

[0068] The battery of the present invention has excellent cycle performance and safety performance.

[0069] In some embodiments, a battery includes the above-mentioned positive electrode sheet, negative electrode sheet, separator and electrolyte.

[0070] The following is a collection of specific embodiments and comparative examples to further explain the invention.

[0071] Example 1

[0072] A method for preparing a positive electrode material comprises the following steps:

[0073] (1) Preparation of positive electrode matrix material Na 0.59 Mn 0.8 Co 0.2 O2: Weigh a certain stoichiometric ratio of sodium acetate, manganese acetate tetrahydrate and cobalt acetate tetrahydrate for ball milling. The dispersant is anhydrous ethanol, the dispersion medium is zirconium oxide, argon is filled as a protective gas, the speed is 300r / min, and the time is 12h. After the ball milling is completed, the mixed slurry is washed out with anhydrous ethanol and placed in a blast drying oven at 80°C to dry. Then grind and disperse in a mortar to obtain a powder mixture. Put it in a muffle furnace, pre-burn it at 500°C for 4h, and calcine it at 900°C for 12h. After that, it is naturally cooled to below 100°C, taken out and ground and dispersed in a mortar to obtain a sodium ion battery positive electrode matrix material.

[0074] (2) Weigh 0.8 g of NaOH and 6.4 g of water to prepare a sodium hydroxide aqueous solution. Weigh 1.188 g of NiCl2·6H2O, add it to 100 mL of ethanol, then add 20 g of the above-mentioned positive electrode matrix material, and ultrasonicate for 20 minutes to dissolve and disperse it evenly. Then, add the sodium hydroxide aqueous solution dropwise into it under mechanical stirring for 10 minutes. After the addition is completed, continue stirring for 2 hours at a stirring temperature of 30°C. Then centrifuge and filter the above suspension, and dry it at 80°C for 12 hours. Then put the powder mixture into a muffle furnace and calcine it at 450°C for 10 hours. Then naturally cool it to below 100°C, take it out and grind it in a mortar to obtain a nickel oxide-modified sodium ion battery positive electrode material.

[0075] Example 2

[0076] A method for preparing a positive electrode material comprises the following steps:

[0077] (1) Preparation of positive electrode matrix material: Na 0.667 Mn 0.9 Mg 0.1O2, weigh sodium carbonate, manganese carbonate and magnesium oxide in a certain stoichiometric ratio and ball mill them, and the rest of the preparation method is the same as that in Example 1.

[0078] (2) Weigh 1.201 g of urea and 9.6 g of water to prepare a urea aqueous solution. Weigh 2.377 g of NiCl2·6H2O, add it to 150 mL of n-butanol, then add 20 g of the above-mentioned positive electrode matrix material, and ultrasonicate for 30 minutes to dissolve and disperse it evenly. Then, add the urea aqueous solution dropwise into it under mechanical stirring for 20 minutes. After the addition is completed, continue stirring for 8 hours at a stirring temperature of 80°C. The above suspension is centrifuged and filtered, and dried at 80°C for 12 hours. Then put the powder mixture into a muffle furnace and calcine it at 600°C for 4 hours. Then naturally cool it down to below 100°C, take it out and grind it in a mortar to obtain a nickel oxide-modified sodium ion battery positive electrode material.

[0079] Example 3

[0080] A method for preparing a positive electrode material comprises the following steps:

[0081] (1) Preparation of positive electrode matrix material Na 0.9 Mn 0.7 Fe 0.2 Cu 0.1 O2: Sodium carbonate, manganese carbonate, iron oxide and copper oxide in a certain stoichiometric ratio were weighed and ball-milled. The rest of the preparation method was the same as that in Example 1.

[0082] (2) Weigh 3.18g of Na2CO3 and 25.4g of water to prepare a sodium carbonate aqueous solution. Weigh 4.362g of Ni(NO3)2·6H2O, add it to 200mL of ethanol, then add 20g of the above-mentioned positive electrode matrix material, and ultrasonicate for 40min to dissolve and disperse it evenly. Then, add the sodium carbonate aqueous solution dropwise into it under mechanical stirring for 30min. After the addition is completed, continue stirring for 10h at a stirring temperature of 50℃. Then centrifuge and filter the above suspension, and dry it at 80℃ for 12h. Then put the powder mixture into a muffle furnace and calcine it at 450℃ for 10h. Then naturally cool it to below 100℃, take it out and grind it in a mortar to obtain a nickel oxide-modified sodium ion battery positive electrode material.

[0083] Example 4

[0084] A method for preparing a positive electrode material comprises the following steps:

[0085] (1) Preparation of positive electrode matrix material NaMn 0.8 Cu 0.15 Li 0.05O2: Sodium carbonate, lithium carbonate, manganese carbonate and copper oxide in a certain stoichiometric ratio were weighed and ball-milled, and then the method for preparing the positive electrode matrix material was the same as that in Example 1.

[0086] (2) Weigh 1.402g of NH3·H2O and 11.2g of water to prepare an ammonia solution. Weigh 2.908g of Ni(NO3)2·6H2O, add it to 150mL of isopropanol, then add 20g of the above-mentioned positive electrode matrix material, and ultrasonicate for 30min to dissolve and disperse it evenly. Then, add the ammonia solution dropwise into it under mechanical stirring for 20min. After the addition is completed, continue stirring for 4h at a stirring temperature of 40℃. Then centrifuge and filter the above suspension, and dry it at 80℃ for 12h. Then put the powder mixture into a muffle furnace and calcine it at 500℃ for 8h. Then naturally cool it down to below 100℃, take it out and grind it in a mortar to obtain a nickel oxide-modified sodium ion battery positive electrode material.

[0087] Example 5

[0088] A method for preparing a positive electrode material comprises the following steps:

[0089] (1) The positive electrode substrate material is the same as that in Example 4.

[0090] (2) Weigh 2.804 g of NH3·H2O and 22.4 g of water to prepare an ammonia solution. Weigh 5.816 g of Ni(NO3)2·6H2O, add it to 200 mL of isopropanol, then add 20 g of the above-mentioned positive electrode matrix material, and ultrasonicate for 40 min to dissolve and disperse it evenly. Then, add the ammonia solution dropwise into it under mechanical stirring for 30 min. After the addition is completed, continue stirring for 8 h at a stirring temperature of 40 ° C. Then, centrifuge and filter the above suspension, and dry it at 80 ° C for 12 h. Then, put the powder mixture into a muffle furnace and calcine it at 500 ° C for 8 h. Then, naturally cool it down to below 100 ° C, take it out and grind it in a mortar to obtain a nickel oxide-modified sodium ion battery positive electrode material.

[0091] Example 6

[0092] A method for preparing a positive electrode material, which differs from Example 4 in that:

[0093] The temperature of the powder mixture in the muffle furnace is 650° C., and other conditions are the same as those in Example 4.

[0094] Comparative Example 1

[0095] The positive electrode material of this comparative example is the positive electrode matrix material NaMn prepared in Example 4. 0.8 Cu 0.15 Li 0.05 O2.

[0096] Comparative Example 2

[0097] A method for preparing a positive electrode material, using a solid phase method, comprises the following steps:

[0098] Weigh 0.582g of Ni(NO3)2·6H2O and 2g of the positive electrode matrix material NaMn 0.8 Cu 0.15 Li 0.05 O2 is added to the ball mill of the planetary ball mill, the dispersant is anhydrous ethanol, the ball milling medium is zirconium oxide, and argon is filled as the protective gas. Ball milling for 4 hours. After the ball milling is completed, the mixed slurry is washed out with anhydrous ethanol and placed in a blast drying oven at 80°C to dry. Take it out and grind and disperse it in a mortar. Put the powder mixture into a muffle furnace and calcine it at 500°C for 8 hours. After that, it is naturally cooled to below 100°C, taken out and ground in a mortar to obtain the positive electrode material.

[0099] Experimental example

[0100] The positive electrode material of Example 4 was ultrasonically dispersed in anhydrous ethanol, and 2 drops were dropped onto a copper grid and dried, and TEM characterization was performed, as shown in FIG. Figure 1 As shown. It can be seen that a single nanosheet of the positive electrode material has a nickel oxide modification layer on its surface. The material of Example 5 was also characterized by TEM, as shown Figure 2 As shown. Figure 1 In comparison, the thickness of the nickel oxide modified layer increases, which indicates that the thickness of the modified layer can be controlled by changing the amount of nickel source.

[0101] The positive electrode materials prepared in Examples 1 to 6 and Comparative Examples 1 to 2 were respectively made into positive electrode sheets, including: weighing the positive electrode material, the conductive agent acetylene black, and the binder polyvinylidene fluoride according to a mass ratio of 8:1:1, pouring them into a mortar and grinding them evenly, then adding an appropriate amount of dispersant N-methylpyrrolidone, and continuing to grind until a uniform slurry is formed. Then, the slurry is evenly coated on the aluminum foil with a scraper coater, and the surface NMP is dried in an 80°C blast drying oven, and then placed in a vacuum drying oven to remove the residual NMP, the temperature is 120°C, and the drying is carried out for 12 hours. Then, it is cut into electrode sheets with a diameter of 11 mm using a punching machine. It is compacted under a pressure of 8MPa on a tablet press to obtain the obtained positive electrode sheet.

[0102] The above positive electrode sheets were assembled into a sodium ion half-cell in a glove box. A button cell shell of CROOD CR2032 was used, and the negative electrode was a metal sodium sheet with a diameter of 14 mm. The solute of the electrolyte was 1 mol / L sodium perchlorate, the solvent was fluoroethylene carbonate and propylene carbonate, the volume ratio was 3:97, and the amount of electrolyte was 150 μL. The diaphragm was Whatman GF / D type glass fiber. The sealing pressure of the battery was 50 MPa. After the assembled button half-cell was left for 8 hours, the electrochemical performance test was carried out after the electrolyte was fully infiltrated and the open circuit voltage was stable.

[0103] The button-type half-cell samples assembled with the positive electrode materials of Examples 1 to 6 and Comparative Examples 1 to 2 were charged and discharged for 100 cycles at a voltage range of 2-4 V and a rate of 0.1C, and were charged and discharged for 500 cycles at a rate of 1C to test their cycle stability. The electrochemical performance test results are shown in Table 1.

[0104] Table 1 Electrochemical performance test results of the battery

[0105]

[0106]

[0107] As can be seen from Table 1, after nickel oxide modification, the capacity retention rate of the battery obtained from the positive electrode material in each embodiment after 100 cycles at 0.1C is improved compared with the battery obtained from the positive electrode material in the corresponding comparative example. This is because a stable solid electrolyte interface is formed, which inhibits the occurrence of surface side reactions and the dissolution of manganese ions, and improves the cycle stability of the positive electrode material. The capacity retention rate at 1C and 500 cycles is also significantly improved, because the nickel oxide modification layer inhibits the cracking and crushing of the particles to a certain extent, while improving the pseudocapacitive behavior of the electrode reaction, and the kinetic performance of the electrode is improved.

[0108] From the electrochemical performance of the positive electrode materials of Examples 4 and 6, the initial discharge capacity of Example 6 is improved. This is because the calcination temperature is increased, the amount of nickel ions doped into the positive electrode matrix material is increased, and the maximum discharge capacity of the electrode is increased.

[0109] It can be seen from Example 4 and Comparative Example 2 that the nickel oxide modified material prepared by the uniform precipitation method of the present invention is superior to the material prepared by the ordinary ball milling solid phase method. The battery cycle stability of Example 4 prepared by the uniform precipitation method is more improved and the capacity is improved.

[0110] In summary, the present invention prepares a layered oxide positive electrode material for sodium ion batteries modified with nickel oxide by a uniform precipitation method. The nickel oxide modified layer inhibits the cracking and crushing of particles, and the solid electrolyte interface formed with the electrolyte inhibits the occurrence of surface side reactions and the dissolution of manganese ions, and the cycle stability of the material is also improved. At a higher calcination temperature, a small amount of nickel ions are doped into the positive electrode matrix material, which increases the maximum discharge capacity of the electrode.

[0111] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positive electrode material, characterized in that: The invention comprises a positive electrode matrix material and a nickel oxide modification layer located on the surface of the positive electrode matrix material; the positive electrode matrix material comprises a layered transition metal oxide material, and the chemical formula of the layered transition metal oxide material is Na q M b D c O2, wherein 0.59≤q≤1, 0.7≤b≤1, 0≤c≤0.3, and b+c=1, M is a transition metal element, and D is a metal doping element.

2. The positive electrode material according to claim 1, characterized in that The transition metal element includes at least one of Cr, Mn, Fe, Co, Ni and Cu; and / or, the metal doping element comprises at least one of Li, Mg, Al, Zn, K, Ca, V, Ti, Nb, Zr and Sn; And / or, the molar ratio of elemental nickel in the nickel oxide modification layer to the positive electrode matrix material is (0.05-0.1):

1.

3. The positive electrode material according to claim 1, characterized in that The layered transition metal oxide material is a layered manganese-based oxide material, and the chemical formula of the layered manganese-based oxide material is Na x Mn y M z O2, wherein 0.59≤x≤1, 0.7≤y≤1, 0≤z≤0.3, and y+z=1, and M is at least one of Fe, Co, Cu and Mg.

4. The method for preparing a positive electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: A nickel compound solution is first mixed with a positive electrode matrix material to obtain a first system; performing a second mixing of the first system and a precipitant solution to obtain a second system; The second system is subjected to solid-liquid separation, and the solid is collected and subjected to heat treatment.

5. The method for preparing the positive electrode material according to claim 4, characterized in that: The nickel-containing compound comprises at least one of nickel chloride, nickel nitrate, nickel chloride hydrate and nickel nitrate hydrate; And / or, the nickel-containing compound solution comprises a nickel-containing compound and an alcohol solvent; And / or, the mass ratio of the nickel-containing compound to the positive electrode matrix material is (1-4.5): (15-25); And / or, the first mixing is carried out by ultrasonic treatment, and the time of the ultrasonic treatment is 10 to 40 minutes.

6. The method for preparing the positive electrode material according to claim 4, characterized in that: The precipitant solution includes an ammonia solution, a urea solution, an ammonium bicarbonate solution, a sodium carbonate solution or a sodium hydroxide solution; and / or, the concentration of the precipitant solution is 1 to 4 mol / L; And / or, the mass ratio of the precipitant to the nickel-containing compound is (0.4-0.8):1; And / or, the second mixing specifically includes: dropping the precipitant solution into the first system, and then performing a third stirring to obtain the second system.

7. The method for preparing the positive electrode material according to claim 6, characterized in that: The temperature of the system for the second mixing of the first system and the precipitant solution is controlled to be 30 to 80° C., and the time of the dropwise addition is 10 to 60 minutes; And / or, the third stirring time is 2 to 10 hours.

8. The method for preparing the positive electrode material according to claim 4, characterized in that: The heat treatment temperature is 450-600°C and the heat treatment time is 4-10h; And / or, the atmosphere of the heat treatment is air; And / or, before the heat treatment, the solid is dried at a temperature of 60 to 90° C. and for a time of 9 to 15 hours.

9. A positive electrode sheet, characterized in that: The positive electrode material comprises the positive electrode material according to any one of claims 1 to 3.

10. A battery, characterized in that: Including the positive electrode sheet as described in claim 9.